2016
DOI: 10.1016/j.jor.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Is depression associated with functional recovery after hip fracture in the elderly?

Abstract: This study results showed that depression had a negative effect on the daily activity level of these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The results are consistent with prior studies demonstrating that longer periods of depressive symptoms after hip fracture are associated with greater decreases in physical function . Yet, the results diverge from prior research and show temporal trends illustrating nonlinear effects of persistent depressive symptom on gait speed over time.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results are consistent with prior studies demonstrating that longer periods of depressive symptoms after hip fracture are associated with greater decreases in physical function . Yet, the results diverge from prior research and show temporal trends illustrating nonlinear effects of persistent depressive symptom on gait speed over time.…”
Section: Discussionsupporting
confidence: 80%
“…Depressive symptoms develop in approximately 50% of the many older adults who annually experience a hip fracture, an acute medical event that is associated with excess morbidity and mortality . Research has consistently demonstrated that postfracture depressive symptoms are associated with greater functional disability . Therefore, depressive symptoms are an important sequela and their deleterious impact on functional recovery may account (in part) for why 50–75% of hip fracture patients never regain their prefracture physical function .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the recovery programmes for a patient after a hip fracture should not solely focus on the physical aspects and that practitioners can potentially make a meaningful impact on a patient's recovery by attending to social factors. Hip fracture management should not be limited to only surgery and physical rehabilitation, but social support and psychiatric disorders could also be addressed as needed (Atay, Aslan, Burc, Demirci, & Atay, 2016 (Allegrante et al, 2007;Cobey et al, 1976;Cree et al, 2001;Cresci, 2001;Magaziner et al, 1990;Oh & Feldt, 2000) and 2 did not (Egan et al, 1992;Marottoli et al, 1992).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Therefore, we can say that a vicious circle of low ADL is created between pre-existing depression and an increase in depression that feelings of inadequacy when performing daily activities can produce. The Geriatric Depression Scale (GDS) may be a valuable instrument by which to assess depression [49]. Depression was observed more often in females and those who had lost their spouses [11].…”
Section: Depressionmentioning
confidence: 99%